Intra- and interspecific variation along environmental gradients: adaptation, plasticity, and range limits - Torres Dowdall, Julián R., author; Ghalambor, Cameron K., advisor; Angert, Amy L., committee member; Fausch, Kurt D., committee member; Poff, N. LeRoy, committee member; Thomas, Stephen, committee member (Colorado State University. Libraries, 2012)
Understanding the processes underlying patterns of intraspecific variation, and how these processes in turn shape the distributional limits of species is a fundamental goal of evolutionary ecology. The study of species distributed along environmental gradients provides a framework for testing how changing conditions lead to local adaptation, phenotypic plasticity, and ultimately shape distributional limits. Yet, environmental gradients are complex, being composed of a diversity of abiotic and biotic factors that act on individual species and shape the interactions between them. Thus, empirical studies aimed to understand patterns of intraspecific divergence and interspecific diversity need to evaluate the effects of both abiotic and biotic factors varying along gradients. Evolutionary ecologists have become increasingly interested in trying to understand the costs and limits to trait variation along environmental gradients and what factors prevent species from evolving larger geographic ranges. Theory predicts that species distributed along environmental gradients should track conditions through local adaptation or adaptive phenotypic plasticity, and that a disruptive factor along the gradient (e.g. increase in the steepness of the gradient, the presence of a competitor, etc.) could result in the formation of distribution limits as conditions become unsuitable for populations persistence. Empirical studies analyzing large-scale patterns of phenotypic variation have provided support for the formation of clines in response to environmental gradients. However, less evidence has accumulated for the formation of such patterns at local scales and clear disruptive factors leading to distributional limits remain elusive. My dissertation takes an evolutionary ecological perspective to understand how environmental gradients shape patterns of variation within and between species. Here, I attempt to understand how abiotic and biotic factors interact to drive patterns of phenotypic variation. To approach this question, I used as a study system two closely related, ecologically similar, and parapatric species of poeciliids distributed along rivers on the island of Trinidad, West Indies. In the first part of this dissertation, I focus on the patterns of intraspecific variation in the Trinidadian guppy (Poecilia reticulata) along a predation risk gradient. I used this species to explore the spatial scale at which local adaptation occurs (Chapter 1), and to investigate the role of adaptive phenotypic plasticity in allowing species to track local optima (Chapter 2). I found that local adaptation in Trinidadian guppies occurs at a smaller spatial scale than previously shown. My results also suggest that adaptive plasticity plays an important role in allowing Trinidadian guppies to track local optima along a gradient of predation risk. Furthermore, I found divergence in patterns of plasticity between Trinidadian guppy populations adapted to low- or to high-levels of predation pressure. My results suggest that this difference in adaptive phenotypic plasticity evolved as a by-product of adaptation to local environmental conditions. In the second part of my dissertation I change my focus from patterns of intraspecific variation to patterns of interspecific variation along environmental gradients. I examine how the Trinidadian guppy and its sister species, the swamp guppy (P. picta), are distributed along a complex environmental gradient in lowland rivers of Trinidad (Chapter 3), and performed a series of experiments aimed to determine what factors drive their distributions (Chapter 4). As Trinidadian rivers approach the ocean, several factors change in comparison to upstream localities, including changes in productivity, physicochemical conditions, and community composition. I found that the Trinidadian guppy and the swamp guppy show an overlapping parapatric distribution along the interface between brackish-freshwater in the lowland rivers of Trinidad. The swamp guppy is usually found in downstream sections of the rivers, both in fresh- and brackish water. On the other hand, the Trinidadian guppy is only found in freshwater, dropping off abruptly at the brackish-freshwater interface. Field and laboratory experiments suggest that brackish water environments are physiologically stressful for the two study species, as survival and growth rate in this environment were lower compared to that observed in freshwater. Also, these experiments indicate that the Trinidadian guppy is competitively dominant over the swamp guppy across all salinity conditions. Thus, I showed that asymmetric competition limits the competitively subordinate swamp guppy to the harshest end of the salinity gradient, and that stressful salinity conditions limits the dominant Trinidadian guppy to the less stressful freshwater end of the gradient.
Keywords: environmental gradient; salinity; local adaptation; plasticity; asymmetric competition; Poecilia